Communicative strategies and tactics in the speech of Liera Farkash, the heroine of the first season of the TV series Early Swallows - Bobro, Mariia; Demianiva, Kateryna (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
Communication plays an extremely important role in the life of humans as social beings. The speech of characters in literary works is promising in terms of studying their communicative behavior, since, on the one hand, it reflects the actual speech of a particular period, and on the other, it is to some extent more deliberate, as  the author, in order to realise their creative intention, meticulously thinks over the characters’ words, the linguistic means they use, the style and nature of their communication. The present article considers the communicative strategies and tactics in the speech of Lera Farkash, the main character of the TV series Early Swallows,  as well as the linguistic means that facilitate their implementation. Theoretical approaches to the classification of communicative strategies and tactics have been characterized. It is pointed out that primarily confrontational (based on opposition and carrying out discussions from a competitive or conflictual standpoint) and cooperative (based on the principles of mutual support, collaboration, and joint problem-solving) strategies are characteristic of Lera’s speech. It has been discovered that initially the confrontational strategy predominates in the girl’s communicative behavior in her interactions with her parents and classmates of a lower social status, which shows through application of communicative tactics of provocation, ignoring, offense, and discreditation aimed at psychological pressure on the interlocutor and diminishing their social status. These tactics are implemented in Lera’s speech through the use of coarse vocabulary, ironic and sarcastic use of diminutive-affectionate forms, provocative rhetorical questions etc. On the other hand, as the plot develops, when Lera starts to communicate with her classmates more closely, becomes more open and trustful with her parents and friends, her behavior increasingly tends to employ cooperative strategies, implemented through the tactics of compliments, openness, and consolation, aimed at supporting and soothing in difficult situations.